Tailoring mineralocorticoid receptor antagonist therapy in heart failure patients: are we moving towards a personalized approach?. (12th April 2017) - Ferreira, João Pedro; Mentz, Robert J.; Pizard, Anne; Pitt, Bertram; Zannad, Faiez
Abstract: The aim of personalized medicine is to offer a tailored approach to each patient in order to provide the most effective therapy, while reducing risks and side effects. The use of mineralocorticoid receptor antagonists (MRAs) has demonstrated major benefits in heart failure with reduced ejection fraction (HFrEF), results with challenging inconsistencies in heart failure with preserved ejection fraction (HFpEF), and 'neutral' preliminary results in acute heart failure. Data derived from landmark trials are generally applied in a 'one size fits all' manner and the development and implementation of more personalized MRA management would offer the potential to improve outcomes and reduce side effects. However, the personalization of pharmacotherapy regimens remains poorly defined in the cardiovascular field (in light of current knowledge) and until further trials targeting specific subpopulations have been conducted, MRAs should be provided to the great majority of HFrEF patients in the absence of contraindication. Spironolactone should be considered for symptomatic HFpEF patients with elevated natriuretic peptides. In the near future, trials should target HFrEF patients using exclusion criteria sourced from landmark trials (e.g. severe renal impairment), select more homogeneous HFpEF populations (e.g. with elevated BNP and structural abnormalities on echocardiography), and determine which patients are likely to benefit from MRAs (e.g. according to prespecified biomarkers).